Comparison of shortwave radiation dynamics between boreal forest and open peatland pairs in southern and northern Finland - Peräkylä, Otso; Rinne, Erkka; Ezhova, Ekaterina; Lintunen, Anna; Lohila, Annalea; Aalto, Juho; Aurela, Mika; Kolari, Pasi; Kulmala, Markku (Copernicus Publications, 2024)
Snow cover plays a key role in determining the albedo, and thus the shortwave radiation balance, of a surface. The effect of snow on albedo is modulated by land use: tree canopies break the uniform snow layer, and lower the albedo, as compared to an open ground. This results in a higher fraction of shortwave radiation being absorbed in forests. At seasonally snow-covered high latitudes, this lowering of the albedo has been suggested to offset some or all of the climate cooling effect of the carbon stored by forests. We used long-term in situ measurements to study the albedo and shortwave radiation balance of two pairs of sites, each consisting of an open peatland and a forest. One pair is located in northern and one in southern Finland in the boreal zone. We found that both forest sites had a low, constant albedo during the snow-free period. In contrast, both peatland sites had a higher snow-free albedo, with a clear seasonal cycle. This seasonal cycle was presumably caused by changing near-infrared albedo, as the albedo for photosynthetically active radiation was considerably more constant over the season. During the snow-covered period, the peatland sites again had higher albedo than the forest sites. The transition between the high and low albedo upon snow accumulation and especially snowmelt was more abrupt at the peatland sites. The annual difference in absorbed shortwave radiation between the peatland and the forest site was greater in the northern site pair, due to longer snow cover duration. This was partially offset by the greater difference in snow-free albedos at the southern site pair. Annual variation in the differences in absorbed shortwave radiation between forest and peatland sites was mainly controlled by the snow melt date at the peatland sites. These findings have implications for the future climate, as snow cover continues to evolve under global warming.